Two new species of the nominotypical subgenus Gonioctena Chevrolat, 1836, from China and Laos, and a proposed new species-group (Coleoptera: Chrysomelidae: Chrysomelinae) - Cho, Hee-Wook (Zootaxa, 2022)
The Gonioctena kanfani species-group of the nominotypical subgenus Gonioctena Chevrolat, 1836 is proposed and reviewed. This group comprises the following five species, including two new to science, distributed in eastern China and northern Laos: G. kanfani (Chen, 1941), G. kamikawai (Chûjô, 1958), G. fujiana Cho & Borowiec, 2016, G. jolantae new species, and G. lukasi new species. Members of this species-group are easily distinguished from other species by their metallic lustre, two yellowish-brown markings on the elytral humeri, and the trifurcated tip of the flagellum of the aedeagus. Photographs of habitus, illustrations of male genitalia, and diagnostic characters for each species are given. A distribution map and literature records are also provided.